Growing up sex in the sixties - Doggett, Peter 1957- (The Bodley Head, 2021)
For this wide-ranging and eye-opening survey of the sexual landscape of the 1960s Peter Doggett has assembled a dozen little-known stories that reveal how the sexual revolution transformed people's lives. This book provides an honest, often disturbing portrait of a constant battle between two forces: the urge to free the body from guilt and restraint; and the desire to control, cannibalise and exploit that liberation for profit or pleasure
Keywords: sex / 1960-1969; seksualitet / 1960-1969; seksualsociologi / 1960-1969; seksuel frigørelse / 1960-1969; historie / 1960-1969